Isovolumetric synthesis of chromium carbide for selective laser reaction sintering (SLRS). (September 2019) - Peters, Adam B.; Zhang, Dajie; Brupbacher, Michael C.; Hernandez, Alberto; Nagle, Dennis C.; Mueller, Tim; Spicer, James B.
Abstract: A novel synthesis approach for the in-situ formation of isovolumetric non-oxide ceramics was demonstrated for application with selective laser sintering additive manufacturing (SLS-AM) methods. By optimizing the ratio of a metal/metal-oxide precursors system, the conversion of a 86/14 molar Cr/Cr2 O3 composite precursor film to Cr3 C2 by gas-solid reaction with CH4 was investigated as a model reaction synthesis process. The composite precursor mixture was ball-milled to nano/micro-sizes to enhance gas-phase mass transport for conversion. The feedstock was deposited as a 250 μm thick film representative of a single SLS layer using a high-volume low-pressure spray deposition method. The effects of H2 and trace amounts of oxidizing gas impurities on the reaction thermodynamics of the conversion process and microstructural evolution were investigated. The gas-solid reactions were carried out at 950 °C with an isothermal dwell time of 0.1 h under atmospheres of Ar/H2 /CH4 and Ar/CH4. The results suggest that expeditious and thorough conversion of the precursor to Cr3 C2 was achieved (greater ≥90 wt% in Ar/CH4 and ≥95 wt% in Ar/H2 /CH4 ). Phase characterization of sample cross-sections using SEM image contrast methods were used to assess apparent volumetric occupancy of the as-deposited Cr/Cr2 O3 precursor film and the Cr3 C2 product ceramic. Results indicate approximate fill fractions of 81.3% (SD = 1.78) and 78.9% (SD = 1.52) respectively, suggesting near isovolumetric conversion. Ultimately, the results in this model system demonstrate isovolumetric reaction syntheses techniques broadly applicable for in-situ non-oxide ceramic production via selective laser sintering-AM. Graphical abstract: Unlabelled Image Highlights: The in-situ synthesis of isovolumetric Cr3C2 was demonstrated for application with selective laser sintering (SLS) additive manufacturing. Isovolumetric Cr3C2 was formed from 86/14 molar Cr/Cr2O3 composite precursor by gas-solid reaction with CH4. The effects of H2 and oxidizing impurities on reaction thermodynamics and microstructural evolution were investigated. SEM image analysis indicates near isovolumetric conversion was achieved for conversion of the Cr/Cr2O3 precursor to the Cr3C2 product ceramic.